Joonas Kokkonen’s “Free” Dodecaphonic Composition? A Study of the Passacaglia from the String Quartet No. 2 - Jurkowski, Edward (Svensk tidskrift för musikforskning / Swedish Journal of Music Research, 2000)
This paper challenges the prevalent notion that such features as multiple row orderings, incomplete row statements, and harmonies which seem to bear no relationship to a precompositionally assumed row ordering in the dodecaphonic compositions by the Finnish composer Joonas Kokkonen are the result of a deliberate disregard of the compositional practices of such classical dodecaphonic composers as Schoenberg and Webern. Rather, Kokkonenís works are seen to contain a highly sophisticated and imaginative use of the twelve-tone system, where dodecaphonic procedures are not compositional ends in themselves but, instead, serve larger structural intentions in a work.